DISTRIBUTION OF ZAKAT FOR CORRECTIONAL INMATES AS AZNAF RIQAB AT BAZNAS OF BARRU DISTRICT - Zainuddin Zainuddin; Salle Salle (Fakultas Hukum, Universitas Diponegoro, 2023)
Riqab in classical terminology is defined as a slave. The legal issue in this study is the interpretation of riqab law to make it more contextual. The purpose of this study is to determine: the meaning of riqab as zakat asnaf at BAZNAS in Barru District, and the distribution of zakat to riqab at BAZNAS in Barru District. This research is an empirical study with a qualitative approach and qualitative descriptive specifications. Data collection was carried out through interviews. BAZNAS of Barru interprets riqab contextually, riqab includes people who are shackled to their freedom because they are in a sentence period. The distribution of zakat to asnaf riqab is addressed to the Correctional inmates in the form of religious guidance consists of religious lectures, tahfidz of the Al-Quran, and skills development by providing capital to the Correctional inmates in the making of bricks.